Investigating the integration of electrodes with the rhizosphere of Oryza sativa through wetland plant microbial fuel cell for sustainable bioenergy production - Pasupathi Mukil Sukitha; Velu Rajesh Kannan (Desalination and Water Treatment)
The P-MFC technology, which acts as an energy source, is one of the promising methods to reduce environmental pollution. In the present study, the P-MFC was constructed using Oryza sativa (Paddy plant), and various electrode materials like carbon, copper, and titanium oxide were used as cathode and aluminum as anode. The experiment was carried out for 34 days. The plant growth was periodically observed and measured, significantly increasing to produce electricity. The highest growth rate was recorded as 52 ± 1.20 cm whereas the power output varies between P-MFCs. The maximum output voltage was obtained as 1320 ± 230 mV in the copper-based P-MFC. The voltage disparity in PMFCs stipulates using different electrode materials in P-MFC systems resulting in assorted competence of electricity production. The analysis of the plant roots after the experiment revealed increased concentration of amino acid and carbohydrate. According to the correlation analysis, the plant growth was indistinguishable from agricultural field plants, which indicates that P-MFC installation does not cause any crop damage. Available Microbial load on electrode material and rhizospheric soil resembles bacterial population-induced power generation. This study demonstrated that P-MFCs with paddy plants and copper electrode are a favorable and assured application for future potential electricity production.